2020
DOI: 10.1109/access.2020.2972622
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Data Hiding Scheme Based on Adjusting Pixel Modulation and Block-Wise Compression for Encrypted Images

Abstract: Reversible data hiding in encrypted image (RDHEI) is a technique that can provide the security and invisibility of their own information during the acquisition and sharing of them among multi-users. Among which, parametric binary tree labelling (PBTL) is a novel technique designed to serve for highcapacity RDHEI. However, considering the local smoothness of the image, its potential redundancy room has not been fully explored. In this paper, we propose an improved PBTL-RDHEI scheme (IPBTL-RDHEI in short). In IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Fig. 11 lists the embedding rates of our scheme and six related works proposed in [18], [19], [20], [21], [22] and [23]. The embedding rates of the proposed scheme outperforms the related works in all cases except for the cover image 'man.'…”
Section: Comparisonsmentioning
confidence: 96%
See 2 more Smart Citations
“…Fig. 11 lists the embedding rates of our scheme and six related works proposed in [18], [19], [20], [21], [22] and [23]. The embedding rates of the proposed scheme outperforms the related works in all cases except for the cover image 'man.'…”
Section: Comparisonsmentioning
confidence: 96%
“…According to the restorability of the cover media, data hiding techniques can be divided into two categories: reversible data hiding [1][2][3][4] and irreversible data hiding [5][6][7]. According to the format of cover images, the data hiding techniques for digital images can be applied to four different domains: the spatial domain [1][2][3][4][5][6][7], the frequency domain [8][9][10], the compressed domain [11,12], and the encryption domain [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we will briefly review some recently reported reversible data hiding in encrypted image works [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and introduce the process of improved Huffman coding using recursive splitting [31].…”
Section: Related Workmentioning
confidence: 99%
“…The RDHEI algorithm allows the data to be embedded into the encryption domain without knowing the original image information or the encryption key, and the original image must be losslessly reconstructed after the information is extracted. The existing RDHEI algorithms can be roughly divided into two categories: reserving room before encryption (RRBE) [15][16][17][18][19][20][21][22][23][24][25] and vacated room after encryption (VRAE) [26][27][28][29][30]. Although researchers have proposed many RDHEI algorithms, there are still some problems to be solved, such as the inability to achieve a high embedding rate, the inability to correctly extract all secret data, the inability to reconstruct image quality well, and others.…”
Section: Introductionmentioning
confidence: 99%